Keragaman Beberapa Aksesi Temu Hitam (Curcuma aeruginosa Roxb.) Berdasarkan Karakter Morfologi - Setiadi, Adi; Khumaida, Nurul; Wahyuning Ardie, dan Sintho (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2017)
Curcuma aeruginosa Roxb. or black turmeric belongs to the family Zingiberaceae is one of the important medicinal plant that is widely distributed in Southeast Asia, including in Indonesia. This plant has been used by the people especially as raw material for medicine and cosmetics industries. However, the development of black turmeric is still constrained by the availability of germplasm collection and improved varieties. The objective of this study was to determine the vegetative morphological characters and phylogenetic relationship among 10 accessions of black turmeric and 3 accessions of genus Curcuma in Indonesia. Data was collected for 15 morphological quantitative characters of black turmeric at the Experimental Garden at Sukamantri IPB based on UPOV and PPVFRA descriptors. The result of principal component analysis has determined three principal components with the proportion of diversity 73.94%. Cluster analysis three clusters accession of black turmeric, namely cluster 1 consisted of accession Cianjur, Malang, Rimbo, and Kendal; cluster 2 consisted of accession Bogor, turmeric (Curcuma longa L.), java turmeric (Curcuma xanthorrhiza Roxb.), Liwa, Natar, white turmeric (Curcuma zedoaria Roscoe.); cluster 3 consisted of accession Cirebon, Kuningan 1, and Kuningan 2. Keywords: cluster, component analysis, germplasm, medicinal plant, phylogenetic